Dampak Pelatihan Digital Marketing dan Keterampilan Komunikasi Terhadap Kesiapan Kerja Mahasiswa di Sektor Digital (Studi Kasus pada Mahasiswa Universitas Islam Malang) - Ayuningtyas, Putri; Khalikussabir, Khalikussabir; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract In the ever evolving digital era, student job readiness is a crucial factor in facing challenges in the workplace. This study aims to analyze the influence of digital marketing and communication skills training on student job readiness in the digital sector. The method used was quantitative research, with data collected through questionnaires distributed to students of the Management Study Program, Faculty of Economics and Business, Islamic University of Malang, intake of 2021, who had participated in digital marketing training. The results of multiple linear regression analysis indicate that digital marketing and communication skills training have a positive and significant impact on student job readiness. The average student job readiness score indicates a fairly high level of readiness. These findings emphasize the importance of integrating digital marketing training and communication skills development into higher education curricula to increase student competitiveness in an increasingly complex job market. This research is expected to provide educational institutions with consideration in designing more effective training programs that align with industry needs. Keywords: Digital Marketing Training, Communication Skills, Job Readiness, Digital Sector.